Constructing an Ideological Discourse of Imaginative Geography in Turkey - V. V. Tsibenko (Международная аналитика)
The author implements the constructivist approach to study the discourse of imaginary geography and its main concepts based on the analysis of the facts of the discourse – the main ideological texts that form the imaginary geography of Turkey in the 19th-21st centuries, and significant events like the publication of maps. The author considers the imaginative geography as a representative and performative discourse of power connected with historical memory and nation-building. The article demonstrates how Turkey, relying on the Turkic and Islamic ideological dominants, uses the technologies of force (G. Fields). State and media mapping is going along with the construction of architecture in territories inhabited by Turks and Muslims, which is carried out at the state level. The analysis showed that at this stage imaginative geography becomes a tool for promoting Turkey’s national interests not only in the post-Ottoman, but also in the post-Soviet spaces. It justifies Turkey’s active foreign policy and legitimizes it in the eyes of people inhabiting this imaginative geography. The inclusion of a religious component expands this geography to a worldwide reach. Through an imaginative geography, relying on the political ideas of Turkism that developed in the twentieth century and underwent Islamization, Turkey projects a new regional configuration, where its role becomes the leading one. Turkey’s active foreign policy includes maintaining its central position through a set of tools, such as humanitarian policy, constructing an imaginary geography and fixing it through the concepts of “geography-destiny” and “geography of the heart”, visualization through mapping. The author comes to the conclusion that although the example of Turkey in the use of imaginative geography is not unique, it demonstrates an example of the successful implementation of the technologies of force and should be taken into account when developing Russia’s foreign policy strategy.